Youth Perspectives on Integrated Youth Services: A Discrete Choice Conjoint Experiment. (July 2022) - Henderson, Joanna; Hawke, Lisa D.; Iyer, Srividya N.; Hayes, Em; Darnay, Karleigh; Mathias, Steve; Thabane, Lehana
Objective: Integrated youth services (IYS) are an emerging model of care offering a broad range of mental health and social services for youth in one location. This study aimed to determine the IYS service characteristics most important to youth, as well as to determine whether different classes of youth have different service preferences, and if so, what defines these classes. Methods: Ontario youth aged 14–29 years with mental health challenges were recruited to participate in a discrete choice experiment (DCE) survey. The DCE contained 12 attributes, each represented by 4 levels representing core characteristics of IYS models. To supplement the DCE questions, demographic information was collected and a mental health screener was administered. Preferences were examined, latent class analyses were conducted, and latent classes were compared. Results: As a whole, participants endorsed the IYS model of service delivery. Among 274 youth, there were three latent classes: 1) the Focused Service (37.6%) latent class prioritized efficient delivery of mental health services. 2) The Holistic Services (30.3%) latent class prioritized a diverse array of mental health and social services delivered in a timely fashion. 3) The Responsive Services (32.1%) latent class prioritized services that matched the individual needs of the youth being served. Differences between classes were observed based on sociodemographic and clinical variables. Conclusions: IYS is an acceptable model of care, in that it prioritizes components that reflect youth preferences. The differences in preference profiles of different groups of youth point to the need for flexible models of service delivery. Service design initiatives should take these preferences into account, designing services that meet the needs and preferences of a broad range of youth. Working locally to co-design services with the youth in the target population who wish to be engaged will help meet the needs of youth.